Humanitas 2022
DOI: 10.32782/humanitas/2022.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Pedagogical Work With Parents to Support Children During the War

Abstract: Професійна діяльність фахівців із соціальної роботи і соціальних педагогів охоплює широкий діапазон соціальних послуг представникам соціально вразливих категорій населення, серед яких вразливі сім`ї, сім`ї, які перебувають у складних життєвих обставинах, кризові сім`ї. Кількість таких сімей значно збільшилась з початком військової агресії Росії в Україні.Ця агресія значно зросла порівняно з 2014 роком після повномасштабного воєнного вторгнення Росії на територію України у лютому 2022 року. Ця війна змусили бли… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A group of authors (Ditkovska, 2013;Slechtova, 2015;Lakkala & Ilomäki, 2015;Pavliuk & Liakh, 2019;Buynytska, 2021;Maussumbayev et al, 2022;Liakh, Lekholetova, Petrovych & Spirina, 2022) carried out a thorough analysis of the importance of training future specialists in the social sphere using ICT and formation their ICT-literacy. The researchers have indicated that the labor market needs qualified specialists who possess a system of knowledge with the possibility of application in related fields, can quickly adapt to technological changes, and are ready to improve their education.…”
mentioning
confidence: 99%
“…A group of authors (Ditkovska, 2013;Slechtova, 2015;Lakkala & Ilomäki, 2015;Pavliuk & Liakh, 2019;Buynytska, 2021;Maussumbayev et al, 2022;Liakh, Lekholetova, Petrovych & Spirina, 2022) carried out a thorough analysis of the importance of training future specialists in the social sphere using ICT and formation their ICT-literacy. The researchers have indicated that the labor market needs qualified specialists who possess a system of knowledge with the possibility of application in related fields, can quickly adapt to technological changes, and are ready to improve their education.…”
mentioning
confidence: 99%